Impact of Superabsorbent Polymer and Irrigation Intervals on Biochemical Characteristics of Tissue Culture- Derived Date Palm Phoenix dactylifera L. cv. Barhi Grown Under Drought Stress - Noor Al-Huda J. Mohsen; Mohammed A.H. Al-Najjar; Dhia A. Taain (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
This study was conducted on 5-year-old tissue culture-derived date palm cv. Barhi to investigate the impact of superabsorbent polymer with three dosages (0, 250, 500) grams per tree and irrigation intervals of (5, 10, 30) days on biochemical characteristics of the leaves. A randomized complete block design was used in a factorial experiment (3x3) with three replicates. Results showed that the 500 g tree‾¹ polymer dosage had a significant effect on total soluble carbohydrates, while the 250 g tree‾¹ polymer dosage was superior to the other dosages in enhancing superoxide dismutase (SOD) enzyme activity. Findings also showed that control treatment (0 g tree‾¹ polymer dosage) was the best in increasing total phenol, peroxidase (POD) activity, amino acids and proline. As for the effect of irrigation periods, the 30-day irrigation interval significantly affected total phenol, SOD and POD activities, amino acids and proline by recording the highest values compared to the rest irrigation periods, whereas the 5-day irrigation period outperformed the others in increasing of total soluble carbohydrates in leaves. The interaction between 0 g tree‾¹ polymer dosage irrigation every 30 days gave the highest rate of proline (10.123 μg g‾¹), while the treatment of 500 g tree‾¹ polymer and the irrigation every 5 days gave the lowest rate (3.897) μg g‾¹.